2001
DOI: 10.1046/j.1525-1497.2001.10117.x
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a first-year primary care experience on residency choice

Abstract: We designed a retrospective cohort study of first-year medical students to assess the impact of a community-based primary care course, Introduction to Primary Care (IPC), on residency choice. In the group that took IPC (n = 282), 48.2% entered generalist residencies (internal medicine, pediatrics, family medicine, or medicine/pediatrics), compared to 38.2% in the group that wanted IPC (n = 398) and 39.6% in the group that did not want IPC (n = 245). Controlling for gender, students who took IPC had a 40% highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 9 publications
2
16
0
1
Order By: Relevance
“…These results were supported by previous reports which showed the importance of a primary care experience for medical students to increase and maintain their motivation for remote area medicine (16,17). Therefore, repeated community -based clinical practices since the early exposure education may be important to increase and maintain the motivation for medicine there.…”
Section: Discussionsupporting
confidence: 90%
“…These results were supported by previous reports which showed the importance of a primary care experience for medical students to increase and maintain their motivation for remote area medicine (16,17). Therefore, repeated community -based clinical practices since the early exposure education may be important to increase and maintain the motivation for medicine there.…”
Section: Discussionsupporting
confidence: 90%
“…Only two studies reduced selection bias by randomly choosing program participants among interested students. One found a significant association between program participation and residency choice, 49 whereas the other suggested that the effect of preexisting interest was a stronger predictor of specialty choice. 56 One study found an additive effect of a preclinical curriculum and a clinical longitudinal preceptorship on students' choice of primary care specialty.…”
Section: Impact Of Interventions On Primary Care Specialty Choicementioning
confidence: 99%
“…Of 21 different programs (described in 26 papers), 15 were primary care courses added to the conventional curriculum. [49][50][51][52][53][55][56][57][58][59][63][64][65][66][68][69][70][71][72] The remaining six programs were special curricula or medical schools focusing on primary care and/or rural health. 47,48,54,[60][61][62] , Contrary to the studies on clerkships, the most frequently studied outcomes of longitudinal programs were career choices after graduation (n=15).…”
Section: Impact Of Interventions On Primary Care Specialty Choicementioning
confidence: 99%
See 1 more Smart Citation
“…A complex set of factors influences medical students' career decisions including gender, race, indebtedness, temperament, and relationship styles [3][4][5][6] . Although specialty preference upon medical school matriculation predicts ultimate career choice, 7 many medical school experiences, especially during clinical rotations, are also influential [8][9][10] . For example, first-year preceptorships with internal medicine faculty and identification of a primary care role model during medical school are associated with a primary care career choice 11,12 .…”
Section: Introductionmentioning
confidence: 99%